(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2016)
Today web is utilized as an essential medium for Business as well as other organizations such as net banking, E-Business etc. Present day attackers targeting such systems are accredited by having control of thousand to million node botnets. Account locking is a customary method to prevent an attacker from attempting multiple passwords for a particular username, enabling convenient login for genuine users while preventing such attacks is a difficult problem. Brute force and dictionary attacks are now well-known and ever growing. In this paper a method is being proposed which defend against online password guessing attacks by using PAPP i.e. Prevent Attack Password Protocol with ATT Test i.e. Automated Turing Test. The PAPP keeps track of information of the user account and its session with the help of a data storage lists. PAPP is a new protocol which uses MAC address of machine each login. If MAC addresses change then user can detect intrusion in between current & previous login.For the password, this system uses the AES algorithm for encryption method to provide more security to previous approach.